Peran Guru Pendidikan Agama Islam dalam Meningkatkan Prestasi Akademik Siswa di SMP Muhammadiyah Lasem - Hana Aulia Salsabila Al Firdaus Qonai; Muhammad Wildan Shohib (Instructional Development Journal, 2026)
In the world of education, teachers have a crucial role in the learning process. Not only as companions but teachers also act as mentors leading to motivation and evaluation of the student learning process. Students' academic potential is inseparable from the role of teachers in it. The aims of this is the role of Islamic Religious Education teachers in efforts to improve student academic achievement at Muhammadiyah Lasem Middle School, to identify supporting factors and obstacles in improving student academic achievement. This study uses a qualitative approach with descriptive methods and in this study uses data collection techniques through interviews, observations and documentation. The results of the study found 1.) Islamic Religious Education teachers are educators who have an important role in the continuity of the learning process, especially in moral development and instilling norms in accordance with the afterlife. Islamic Religious Education teachers are not only limited to conducting learning but have the task of cultivating student character values and can be role models for students. 2.) in efforts to improve academic achievement at Muhammadiyah Lasem Middle School, there are supporting and inhibiting factors including support from the principal and a well-facilitated learning environment that helps children easily develop academic achievement. Furthermore, inhibiting factors include limited learning time and inappropriate learning methods, which can make learning difficult for students, which can negatively impact their academic achievement.